Prevalence and consequences of sport specialization among Little League baseball players - Post, E. G.; Rosenthal, M. D.; Pennock, AS. T.; Rauh, M. J. (Sports Health: A Multidisciplinary Approach, 2021)
Background: Baseball is one of the most popular boy`s youth sports, and there has been a rise in the rates of certain overuse injuries among players. Specialization has been identified as a risk factor for overuse injury in high school athlete populations, but there is little understanding of the prevalence or consequences of sport specialization in Little League baseball players. Hypothesis: Sport specialization will be highly prevalent among Little League baseball players and specialization will be associated with worse throwing arm health. Study Design: Cross-sectional study. Level of Evidence: Level 3. Methods: A total of 246 Little League baseball players (male; N = 241; age, 9.5 ± 1.6 years) between 7 and 12 years old completed an anonymous, online questionnaire with their parent`s assistance. The questionnaire consisted of participant demographics and baseball participation information, including sport specialization status and the Youth Throwing Score (YTS), a valid and reliable patient-reported outcome measure for youth baseball players. Results: Only 29 (11.8%) players met the criteria for high specialization. Approximately one-third of all players (n = 77; 31.3%) reported participating in baseball year-round or receiving private coaching outside of their league (n = 81; 32.9%). Highly specialized athletes demonstrated worse scores on the YTS on average compared with low-specialization athletes (mean [SE]: 56.9 [1.6] vs 61.1 [1.2]; P = 0.01). Similarly, pitching in the previous year (P < 0.01) or traveling overnight regularly for showcases (P = 0.01) were associated with a worse score on the YTS. Conclusion: While the prevalence of high sport specialization was low among Little League baseball players, other behaviors associated with specialization such as year-round play and the receiving of private coaching were more common. Highly specialized Little League players demonstrated worse throwing arm health compared with low-specialization players. Clinical Relevance: Little League players and their parents may represent a potential target audience for dissemination campaigns regarding sport specialization.